Olympics and Paralympics 2012 mass gathering in London: time-series analysis shows no increase in attendances at sexual health clinics. (8th April 2015) - Hall, Victoria; Charlett, André; Hughes, Gwenda; Brook, Gary; Maguire, Helen; Mercer, Catherine H; Coyne, Katherine; Cassell, Jackie; Crook, Paul
Abstract : Objective: To determine whether the 2012 Olympic and Paralympic Games were associated with a change in the number of patients attending or diagnosed with a new sexually transmitted infection (STI) at sexual health clinics in London and Weymouth. Methods: We undertook an interrupted time-series analysis of surveillance data from the Genitourinary Medicine Clinic Activity Dataset (GUMCAD) collected at 33 genitourinary medicine (GUM) clinics in London and Weymouth (where Games events were concentrated) between 2009 and 2012. Mixed-effects linear regression models of weekly attendance and diagnoses, incorporating temporal trends, bank holidays, categorical month and clinic closures, were used to test for the effect of the 'Olympic–Paralympic' period. We subdivided the 9-week 'Olympic–Paralympic' period (16 July 2012 to 17 September 2012) into five periods, including three Olympic weeks, two Paralympic weeks, pre-, post- and inter-Games weeks. We also compared characteristics of patients attending during the Olympic–Paralympic period and those attending during the same period in 2011. Results: During the 3 weeks of the Olympics, there was a significant reduction in the number of new episode attendances (2020 fewer, 5.6% reduction (95% CI −8.2 to −2.9)) and the number of patients diagnosed with an STI (267 fewer, 4.8% reduction (95% CI −8.6 to −0.9)) compared to expected. There were no important differences in the profile of patients attending during the 2012 Olympic–Paralympic period and those attending during the same period in 2011. Conclusions: We conclude that a 'business-as-usual' approach to managing local sexual health clinics during the 2012 Olympic and Paralympics would have been appropriate.